Validation of Neuropad in the Assessment of Peripheral Diabetic Neuropathy in Patients with Diabetes Mellitus Versus the Michigan Neuropathy Screening Instrument, 10g Monofilament Application and Biothesiometer Measurement - Zografou, Ioanna; Iliadis, Fotios; Sambanis, Christos; Didangelos, Triantafyllos (Current Vascular Pharmacology, 2020)
Objective: Sudomotor dysfunction is a feature of Diabetic Peripheral Neuropathy (DPN). The indicator plaster Neuropad can provide an easy and accurate way to diagnose DPN. The aim of the present study was to evaluate Neuropad’s specificity, sensitivity and accuracy in detecting DPN in patients with Diabetes Mellitus (DM). Methods: A total of 174 patients with DM (79 with type 1 DM, 88 women), mean age 49.8 ± 16.1 years and mean DM duration 17.3 ± 7.7 years were included in the present study. The following methods were used to diagnose DPN: the Michigan Neuropathy Screening Instrument Questionnaire and Examination (MNSIQ and MNSIE, respectively), application of 10 g monofilament (MONO) and measurement of vibration perception threshold with biothesiometer (BIO). Neuropad was applied to both feet in all patients and according to the presence or absence of color change of the sticker, patients were divided in two groups: group A (n = 82, complete change in color from blue to pink, depicting normal perspiration) and group B (n = 92, incomplete or no change, depicting abnormal perspiration). Results: MNSIQ and MNSIE were positive for DPN in 111 and 119 patients, respectively. BIO was abnormal in 109 and MONO in 59 patients. Sensitivity of Neuropad testing was 95% vs. MONO, 73% vs. BIO, 73% vs. MNSIE and 75% vs. NSIQ. Specificity was 69, 81, 90 and 92%, respectively and accuracy of the test was 78, 76, 78 and 83%, respectively. Conclusion: Neuropad has a high sensitivity and specificity in detecting DPN vs. MNSIQ, MNSIE and BIO. Neuropad has a high sensitivity but moderate specificity vs. MONO. The accuracy of the test was high in all measurements.
Keywords: sensitivity